Isolation And Physicochemical Properties Evaluation Of Pepsin-Solubilised Collagen And Its Hydrolysate From The Integument Of Sea Cucumber (Stichopus Vastus) - Abedin, Md. Zainul (2014)
Sea cucumber (stichopus vastus) is considered as an underutilised source, since only its stomach and intestines are eaten raw as salad in few asian countries. All other parts including the integument (high content of collagen) are discarded and hence, a valuable by-product having potential food, cosmetic and pharmaceutical applications is wasted. In view of this, the present study was designed to isolate pepsin-solubilised collagen (psc) from the integument of 5. Vastus and to prepare its hydrolysate through trypsin hydrolysis for their potential applications. Sds-page analysis showed that the isolated psc was of type i and consisted of three ai chains with a yield of 21.3%. Fourier transform infrared (ftir) spectroscopy revealed that the structure of triple helix was well preserved in the psc. Amino acid composition showed that glycine was dominant in the psc. Peptide map of the psc digested by v8 protease was different from that of calf skin type i collagen.